The viability of a fully fledged inflation targeting regime in Egypt - Farid, Sarah Samy (AUC Knowledge Fountain, 2018)
Inflation targeting (IT), in simplistic terms, is a monetary policy regime that is based upon the commitment of a country’s monetary authority to meeting predetermined, quantitative targets for the annual rate of inflation. IT has attained popularity and widespread acclamation amongst policymakers in the international context over the past three decades. Since Egypt initiated a new economic and structural reform program supported by the Extended Fund Facility from the IMF in November 2016, the search for a new nominal anchor for the Egyptian economy has been underway. In this regard, the new objective seems to be a temporary switch to a monetary targeting regime in the short run, while moving towards the implementation of a full-fledged IT regime in the medium term. Against this background, the Central Bank of Egypt (CBE) recently released a draft law indicating its desire to transition towards IT. This paper aims to answer the question of whether or not Egypt is ready for the implementation of IT. I propose a twofold methodology based on an assessment of the institutional and technical framework currently in place in Egypt, combined with a comprehensive survey of the current international practices of 28 inflation-targeting countries to determine whether or not the Egyptian framework is adequate in meeting the basic preconditions for IT, and to identify the practical considerations that need to be taken into account if the CBE indeed decides to adopt an inflation targeting regime in the near future.